Innovative Education in Russia - Chernykh, Sergey I.; Parshikov, Vladimir I. (International Journal of Economics and Financial Issues, 2016)
The authors see globalization as a catalyzer of innovative development. Modern innovations develop under conditions of open global economy that has features of an open market, high competition and global communication. This results in intensive interaction between countries, companies and communities in all spheres of economic life. Social and economic modernization and structural changes in Russian society under conditions of globalization are related to the transfer from a natural resources economy to a new stage of social development. This stage is considered as one where information and knowledge play the key role and the generation of new knowledge is based on the systematization of existing knowledge. This type of modernization assumes economic growth; it is the basis for innovations and human resources that conform to the needs of the economy. Mineev notes that it is important to correlate the outputs of national education reform with its adaptive significance and global transformations” (Mineev, 2009). Implementation of this strategy requires a development of the principles that meet this goal. This paper aims to consider these factors. Keywords: Education, development, economy JEL Classifications: I2, I25, P3